Analysis of Nursing Education Curricula in Spain: Integration of Genetic and Genomic Concepts - Estel·la Ramírez-Baraldes; Katerin Ariza-Martin; Daniel García-Gutiérrez; Cristina García-Salido (Nursing Reports, 2024)
The integration of genetics and genomics into nursing practice is essential for addressing genetic pathologies and providing personalized patient care. This study aims to analyze the nursing education curricula across Spanish universities to understand how genetic and genomic concepts are incorporated. Using the “Qué estudiar y dónde en la Universidad” (QEDU) database, an official source provided by the Spanish Ministry of Universities, a systematic review of 4720 teaching guides from 118 university centers was conducted. Our findings reveal that 12 centers do not include any genetic or genomic content, while 43% of the remaining centers focus solely on basic genetics. In contrast, 57% cover advanced topics, such as genetic counseling and pharmacogenetics. Teaching methodologies predominantly involve lectures and seminars, with limited practical training. On average, three to six ECTS credits out of the total 240 required for the Nursing Degree are dedicated to genetics and genomics. This study highlights the need for curriculum updates and standardization to ensure comprehensive training in these crucial areas. Improved integration of genetic and genomic education will better prepare nursing professionals to meet the evolving demands of modern healthcare. This study was not registered.